Effect of Portland Cement on Mechanical and Durability Properties of Geopolymer Concrete at Ambient Temperature - Seick Omar Sore; Yawo Daniel Adufu; Philbert Nshimiyimana; Adamah Messan; Gilles Escadeillas (Salehan Institute of Higher Education, 2023)
Environmental concerns have prompted researchers to focus on the development of alternative building materials like geopolymer concrete. However, their implementation requires curing beyond 60°C, which limits their application on building sites. This study aims to design a geopolymer concrete at room temperature (30 ± 5°C) in a laboratory in Burkina Faso using a metakaolin-based geopolymer binder activated by an alkaline solution of NaOH and natural aggregates. Portland cement type CEM I 42.5 was used by mass substitution (0 to 25%) of metakaolin to promote curing at ambient temperature. The samples were cured for 7 to 28 days and characterized for physical, mechanical, and durability properties. The results showed that the incorporation of 0 to 20% cement significantly improved the compressive strength from 9.9 to 30.5 MPa and the tensile strength from 1.2 to 2.2 MPa. However, Portland cement has various effects on the durability of geopolymer concrete. It reduces the porosity accessible by water from 15 to 13% and decreases the resistance to acid attack by increasing the mass loss from 2 to 7%. This confirms that common concrete types C20/25 or C25/30 can be casted using geopolymer concrete on the sites in Burkina Faso once their durability is confirmed. Doi: 10.28991/CEJ-2023-09-07-04 Full Text: PDF